Neoptiks: visión desfragmentada/invasión espacial - Aune, Karen (CALLE14: revista de investigación en el campo del arte, 2011)
The research-through-creation project Neoptiks: Defragmented vision/Spatial Invasion, consisted in a pictorial installation that takes on space as the possibility of a fictional experience that is conceptually based on the technological advances of our era. Bringing to light the fact that each new technology creates changes in the “techno-aesthetic” device, the relationship between the subjectivity of the artist and the collective mode of perception goes through a "new configuration" that corresponds to its moment in time. This article aims to tell the creative processes of the work.